Discovering regulatory concerns on bridge management: An author-topic model based approach. (March 2019) - Wen, Qi; Qiang, Maoshan; Xia, Bingqing; An, Nan
Abstract: The management of bridges has major influence on the safety of transport system. Bridge management (BM) practices are carried out in compliance with policies and regulations. This study aims to identify the major aspects of BM from policy documents. We conducted a two-round retrieve to construct a comprehensive dataset of 263 related policies and regulations issued in the 31 provinces/municipalities of mainland China in recent 30 years. The Author-Topic Model (ATM) text mining approach was adopted to identify the key topics in the policies. The revealed 12 topics correspond to 12 major aspects of BM. Some topics, such as bridge maintenance and safety responsibility system, are gaining increasing attention in recent years, while the prevalence of some topics, such as bridge maintenance department configuration, is decreasing. The Granger causality tests suggest that remedial measures attract immediate regulatory attention in response to accidents, while proactive measures contribute to bridge collapse accident reduction, however, in a relatively long term. These findings provide practical implications for policy makers by reminding them that proactive measures should be emphasized alongside remedial measures. Highlights: This study reveals 12 key aspects in policies on bridge management (BRM). The prevalence of topics in policies reflects regulatory concerns in recent years. The empirical analysis findings suggest to put more emphasis on proactive BM measures.